Giant non-Schmid effect in NiTi. (September 2017) - Alkan, S.; Wu, Y.; Sehitoglu, H.
Abstract: The work addresses the departure from Schmid law during plasticity of shape memory alloy, NiTi, that has been overlooked despite its cardinal importance. High resolution Digital Image Correlation (DIC) technique is utilized to pinpoint the critical resolved shear stress (CRSS) levels in uniaxial tension and compression experiments. To our knowledge, the non-Schmid behavior of B2 NiTi is characterized for the first time precisely, and the results indicate that the non-glide stresses (both shear and normal character) play a considerable role on yielding. The non-glide stresses affect the core spreading which in turn dictates the changes in CRSS. A generalized yield criterion is proposed to predict the anisotropic experimental response accurately. Graphical abstract: